Peningkatan Keterampilan Rangakaian Listrik Dalam embelajaran IPA Menggunakan Metode Eksperimen Pada Kelas VI MIM PK Kenteng Nogosari Boyolali Tahun 2015/2016 - ISMAIL, Ghufron Taufiq; , Dr. Achmad Fathoni, M.Pd (2016)
Ghufron Taufiq Ismaili/ A510120166. SKILLS ENHANCEMENT OF ELECTRICAL CIRCUITS IN LEARNING USING IPA EXPERIMENTS IN CLASS VI MIM PK KENTENG NOGOSARI BOYOLALI 2015/2016. skripsi. Faculty of teacher training and educational sciences, University of Muhammadiyah Surakarta. March, 2016. This study aims to determine the increase in learning science process skills using the experimental method in class 6 MIM PK Kenteng Nogosari Boyolali. Data collection techniques gained through observation, interviews, documentation and test engineering. Triangulation techniques used in this study is the technique of triangulation with the source. on pre-cycle value of the average grade of 4.25 with the thoroughness klasikan which only reached 26% and has not reached the KKM then with the learning outcomes of this study electrical circuit on the students jump in the number of students who pass the KKM ≥65 meet are as follows: (1) In the pre-cycle, students who meet the KKM only 5 students or 26%. (2) At the first meeting of the first cycle, students who meet the KKM 7 students or 36%. (3) In the first cycle the second meeting, students who meet the KKM 9 students, or 47%. (4) At the first meeting of the second cycle, students who meet the KKM 13 students or 68%. (5) At the second meeting of the second cycle, students who meet the KKM is 16 students from 19 students (84%). From the description it can be concluded that the learning outcomes of the electrical circuit in the sixth grade students MIM PK Kenteng increasing.